Bayesowska procedura wyboru liczby składników mieszanki rozkładów - Biskup, Dariusz (Bayesian procedure for number of components choice in a mixture of distributions, 2008)
The paper describes the Bayesian procedure for the selection of the number of components in a mixture. The numerical implementation involves the Reversible Jump Markov Chain Monte Carlo algorithm (RJMCMC). The Bayesian approach assumes that the model is treated as an unknown parameter over which we can assume a probability distribution. The model and in this case, the number of components in a mixture, is selected according to the criterion of the maximum posterior probability. The first part of the paper presents an analytical solution of the problem for the simplified example of a mixture of binomial distributions. Then the RJMCMC algorithm is described and its implementation for the problem of the choice of the number of components for the Poisson mixture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 41-55